(untitled) (Journal of Educational Sciences, 2016)
It is known that in the predevelopment of a new generation of young people in the organization of educational process the main belongs to the educators. In adressing this conceptual idea is very important teacher professionalism and moral qualities. This article introduces and summarizes the experimental results obtained with the main principles of the state policy, the main elements of the content of education, culture and identity of the head of the institution. The present stage of development of preschool education is characterized by its updating, are updated, modernized system and technologies of educational process. And it, applying new ideas and approaches to the organization of pedagogical process, creates opportunities for formation of children as persons.